What is a doctorate concerning landscape ? - Catherine Chomarat-Ruiz (Projets de Paysage)
Based on the realisation that research concerning the landscape is a fact, that during thirty years seminars have been dedicated to this subject in schools of landscape architecture, this article exposes the problems inherent to the creation of a doctorate concerning the landscape and demonstrates that these problems stem from an object and a disciplinary field that are difficult to define. It then analyses a sample of ground-breaking documents in order to identify the major questions and the attempts at answers that still nourish the field of research in landscape architecture today. It indicates that these ways of conceiving research, the part played by this activity in professional schools, its social role, the field it covers and the disciplines that support it, are often all structured around three oppositions : art/science, usefulness/disinterestedness, creation of a work of art/furthering of knowledge. Lastly, it exposes assumptions concerning the scope of a Doctorate with majors in landscape design, in landscape art criticism and in landscape sciences. It then suggests that by attempting to go beyond these oppositions, which boil down to the nature/culture dichotomy, only a last major concerning a theoretical landscape science would be appropriate.